Study guides

Q: 3x plus 12 equals x plus 48?

Write your answer...

Submit

Related questions

3x+5y=48 5y=48-3x-3x+5y=12 -3x+(48-3x)=12-6x=-36x=65y=48-3(6)5y=30y=6(6,6)

3x + 10x - 48 = 0 13x = 48 x = 3.692307692

The terms in x in the factorisation must be 3 and 1, the whole numbers must be factors of 48 ie 1/48, 2/24, 3/16, 4/12, or 6/8. The only ones which can combine with the 3 to give a sum of 24 are 4 and 12 viz: (3x + 12)(x + 4)

36 + 12 = 48

12 + 12 = 24. 24+12=32. 32 + 12 = 44

(3x-12)(x-4)

144

many solutions

366

it is 72 easy

x = 16 3x = 48 divide both sides by three to get x by itself x=16

3x - 5 = 48 So 3x = 53 and x = 53/3 = 17.66...

48 divided by 12 equals 4. 48/12 = 4

It is 4 1/34.

15x2 + 58x + 48= 15x2 + 18x + 40x + 48= 3x(5x + 6) + 8(5x + 6)= (3x + 8)(5x + 6)

576/48= 12.

This is elementary stuff: 3x + 6 = 54 Subtract 6 from each side: 3x = 48 Divide each side by 3: x = 16.

12(3x-8)=48Distribute the 12 to the 3x and -8, that would give you 36x-96=48Next add the -96 to both sides of the equation resulting in 36x=144Lastly divide both sides of the equation by 36 giving you the result of x=4

3x + 13 = 61 - 3x : add 3x to both sides 6x + 13 = 61 : deduct 13 from both sides 6x = 48 : divide both sides by 6 x = 8

48 + 1 = 49

48 inches plus 4 feet equals 8 feet. 1 foot= 12 inches. 4 feet= 48 inches.

-10 x -6 = 60 60 + -12 = 48

In math problems without punctuation such as brackets, the standard convention in to solve from left to right. Therefore, you would solve the problem 15-3 times 4 plus nine like by three actions. 15-3 equals 12; 12 times 4 equals 48; 48 plus 9 equals 57.

x=4 or x=-4

48